Pengaruh Strategi Pemasaran Terhadap Penjualan di PT Ulam Tiba Halim - Jakarta - Gokmariana Barutu; Danang Aziz Akbarona; Darka (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of Marketing Strategy on Sales at PT. Ulam Tiba Halim – Jakarta. The research method used is quantitative method with descriptive and associative approach. The population in this study amounted to 105 sales personnel. The sample size was determined using the Slovin formula with an error rate of 5%, resulting in a sample of 84 respondents. The sampling technique used was probability sampling. Data collection technique was carried out through distributing questionnaires. Data analysis techniques used include validity test, reliability test, Pearson correlation analysis, coefficient of determination, t-test, and simple linear regression analysis with the help of SPSS version 25 software. The results of the study indicate that Marketing Strategy has a positive and significant effect on Sales. This is evidenced by the t-count value of 2.337 and the significance value of 0.022 < 0.05. The Pearson correlation coefficient value of 0.250 indicates a low relationship. The R Square value of 0.062 or 6.2% indicates that Marketing Strategy contributes 6.2% to Sales, while the remaining 93.8% is influenced by other factors not examined in this study. Based on the results of descriptive analysis, Marketing Strategy is in the High category with an average of 82.93 and Sales is also in the High category with an average of 52.95. However, there is a statement item with the lowest score, namely item number 10